Effect of nickle doping in Sn-Ag-Cu solders on intermetallics formed during soldering on direct immersion gold (DIG) surface finish - Ng, Theng Pin, 1987-; Ali Ourdjini; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2011